Organizational life-cycle analysis of corporate offending: insights into how changes in business cycles interact with regulatory oversight to shape compliance and violations - Wu, Yunmei (Crime, law and social change, 2024)
This paper showcases an organizational life-cycle analysis of corporate offending behavior in small businesses. It analyzes two small food and hospitality firms in China, drawing on deep ethnographic data collected during three years of fieldwork. The paper investigates these two businesses as they go through three phases: pre-existence, existence, and survival. The study shows that organizational life-course analysis is important for understanding the development and root causes of organizational offending. It finds that offending evolves alongside the development of the organization. It shows that an organizational life-cycle analysis should focus not just on changes in the corporation itself, but also on how the regulatory context changes over the course of the organization’s development and maturing. Stages in the business cycle coincide with changes in regulatory encounters, and this shapes how corporations view what regulators expect of them and the extent to which they can violate such expectations. This points to a broader form of life-course analysis. It urges the field to moves beyond an analysis of changes in the business to also study the how such changes coincide with changes in the regulatory frameworks that are supposed to monitor and reduce offending.